A Study Towards Pedestrians’ Usage And Behavior On Footbridge - SYAHRUNNIZAM, MUHAMMAD ADAM HAIQAL; MUHAMAD, NUR HAZIQAH; MOHD SHAHROL, MUHAMMAD HAFIZ; Hamid, Nor Baizura (Multidisciplinary Applied Research and Innovation, 2022)
This study aims to investigate the main factors that influenced of the pedestrian’s behavior during crossing roads. Besides, the study also wants to analyze primary and secondary data that have been collected, and providing beneficial solutions by giving control measures so that pedestrians comply the road safety. For pedestrian who crossing the road without using footbridge, they are more vulnerable to the risk of road accidents Disobedient pedestrian behavior with the use of footbridges will be invite the risk of accidents. Even if the pedestrian is not injured, the action can cause the vehicle owner to be involved in an accident because he wants to avoid colliding with the pedestrian individual. In this study cases, there are two selected different location in Muar District, Johor. The two locations are Astaka Shopping Center Sdn. Bhd and Bentayan Bus Station, Muar. The study site was chosen because it easier to make observations and collected data because it is located in an urban area. The questionnaire method was conducted on 75 respondents of two different locations of study. Data were obtained through primary data which are surveys, observations and interviews.  Data were analysed using descriptive statistics presented in the form of percentage and frequency of used footbridge. The results of the pedestrian safety study among the pedestrians showed that all four variables of pedestrian behavior, road user behavior, authorities’ action and also condition of footbridges were at unsatisfactory levels. 60.7% of the respondents neglects of using footbridge to save time and 94.7% of the respondents said that they never being fined by authorities for not using footbridge to cross the roads. Several recommendations were put forward to improve safety among pedestrians. Cooperation between the government and the community is important in that pedestrians can travel safely while traveling to their destination.